The 2,2',4,4',5,5'-hexachlorobiphenyl-enhanced degradation of connexin 43 involves both proteasomal and lysosomal activities - Simecková, Pavlína; Vondrácek, Jan; Andrysík, Zdenek; Zatloukalová, Jirina; Krcmár, Pavel; Kozubík, Alois; Machala, Miroslav (Toxicological sciences, 2009)
One of the toxic effects of non-dioxin-like polychlorinated biphenyls (NDL-PCBs) is the acute inhibition of gap junctional intercellular communication (GJIC), an event possibly associated with tumor promotion. The model NDL-PCB-2,2',4,4',5,5'-hexachlorobiphenyl (PCB 153)-induces a sustained GJIC inhibition in rat liver epithelial WB-F344 cells. As this effect might be related to deregulation of connexin 43 (Cx43) synthesis, trafficking, or degradation, we investigated the impact of PCB 153 on these events. Although PCB 153 had no effect on Cx43 mRNA levels, it induced a gradual loss of Cx43 protein and significantly decreased the amount of gap junction plaques in plasma membrane. PCB 153 contributed to extracellular signal-regulated kinases 1 and 2 (ERK1/2)-dependent accumulation of hyperphosphorylated Cx43-P3 form, thus indicating that ERK1/2 activation by PCB 153 might contribute to its effects on Cx43 internalization or degradation. Inhibition of either proteasomes or lysosomes with their specific inhibitors largely restored total Cx43 protein levels, thus suggesting that both proteasomes and lysosomes may participate in the PCB 153-enhanced Cx43 internalization and degradation. However, neither the proteasomal nor the lysosomal inhibitors restored normal GJIC or number/size of gap junction plaques. Finally, PCB 153 also interfered with restoration of gap junction plaques following the inhibition of Cx43 transport to plasma membrane. Taken together, multiple modes of action seem to contribute to downregulation of Cx43 in PCB 153-treated rat liver epithelial cells. The enhanced degradation of Cx43, together with persistent inhibition of GJIC, might contribute to tumor-promoting effects of NDL-PCBs.
Keywords: Liver; Analysis of Variance; Animals; Gap Junctions; Metabolic Networks and Pathways; Lysosomes; buněčné linie; leupeptiny; Polychlorinated Biphenyls; játra; inhibitory proteasomu; lyzozomy; polychlorované bifenyly; metabolické sítě a dráhy; mezerový spoj; Cell Line; Proteasome Inhibitors; analýza rozptylu; proteasomový endopeptidasový komplex; Connexin 43; Leupeptins; mezibuněčná komunikace; krysa rodu Rattus; konexin 43; Cell Communication; zvířata; buněčná membrána; extracelulárním signálem regulované MAP kinasy; Rats; Proteasome Endopeptidase Complex; Cell Membrane; Extracellular Signal-Regulated MAP Kinases